Commodity fetishism and objective reality in Sam Shepard’s Curse of the Starving Class - Majeed, Abdulhameed A.; Noor, Rohimmi; Talif, Rosli (Universiti Putra Malaysia Press, 2016)
This article analyzes the class system in Sam Shepard’s Curse of the Starving Class. Class system is scrutinized in terms of the capitalist and proletariat forces in the play. The core argumentative theme emphasises the degenerating labour opportunities in the socio-economic life of American individuals. In essence, the study mainly focuses on the achievement of economic welfare in a poor-economic society. The loss of economic welfare is not sufficiently obtained by the main characters, especially Wesley and Ella who long for economic prosperity and stable social life. These characters do not achieve their aspiration and do not make progressive economic labour. Therefore, the study accentuates the way in which these characters lose their work opportunities. The analysis of this economic loss is done by applying two Marxist concepts, namely, commodity fetishism, and the objective reality of economic societies. Together, these concepts uncover the class struggle in Curse of the Starving Class.